Fotocatálise e suas aplicações em reações de ciclização oxidativa e terapia fotônicas - Lopes, Thais de Assis (2019)
In the chapter 1, studies on photocatalysed reactions were carried out by porphyrins and other photocatalysts aiming at the formation of radicals in amino aromatic systems for subsequent addition reaction. More specifically, double functionalization C-H reaction were studied by oxidative cyclization of N,N-dimethylaniline (16) with N-phenylmaleimide (17) to obtain tetrahydroquinolines, both by SET (single electron transfer) using meso-tetraphenylporphyrin (TPP) and Electron Donor-Acceptor (EDA) complex. For the evaluated reaction, the use of the photocatalyst TPP presented no influence on the formation of the product. Thus, experiments were additionally performed using N, N-dimethylaniline (16) and varying different electrophiles, however, it was not possible to observe the formation of the expected tetrahydroquinolines. Using the substrate fumaronitrile (65) gave a product of interest (2-(methyl(phenyl)amino)acetonitrile) (72), from a radical reaction of N,N-dimethylaniline (16) with fumaronitrile (65). Further, exploratory optimization experiments were performed, but unsuccesfully. Due to the appearance of related publications in the literature, it was decided to no longer insist on these studies. In the chapter 2 the synthesis and photophysical studies of hybrid molecules between curcumin (6) and bixin (11) were carried out aiming at the production of some new photosensitizing molecules for PDT applications. Curcumin is a compound well known by our research group with a well-established synthesis. Bixin (11) was extracted from the seeds of annatto by a modified methodology established in the literature. After obtaining these starting materials, the syntheses of chimeric photosensitizing molecules, the dimer (25) and the trimer (26) were studied. After the syntheses and characterizations of these compounds, studies of their photophysical properties were carried out, namely, studies of molar absorptivity, singlet oxygen quantum yield, photodegradation study, fluorescence quantum yield and aggregation. From these studies it was possible do stablish the molar absorptivities of the products are greater than those of the starting materials. The singlet oxygen quantum yield and the photodegradation of the products showed properties that are similar to bixin (11). Both the dimer (25) and the trimer (26) showed low fluorescence. The trimer (26) exhibited a high Stokes shift. In DMSO the compounds did not present aggregation, but in water the compounds proved to be hydrophobic. Further PDT applications will be performed in order to evaluate the use of these compounds as photosensitizers in PDT ou photodiagnosis.